3 - Mindless versus mindful sociology: Models of mind in sociology and the social sciences - Ken Jubber (African Sociological Review, 2001)
This article deals with the dominant mode! of mind implicit or explicit in many of the social sciences and sociology. Following the lead of evolu tionary psychologists John Tooby and Leda Cosmides, this dominant the ory of mind is referred to as the 'Standard Social Science Madel'. This mode! is described and a short history of it provided. A brief explanation for ifs dominance is also offered. The paper argues that this mode! is now obsolete and that scientific progress in sociology and the social science is being hampered byadherence toit. The major shortcomings f the mode! are identified. An alternate mode[ of mind, the 'Integrated Mode!', is ojfered asa scientifically sounder one that offers sociology and the social sciences a wayout of the rut they are currently in. The mainfeatures of the Integrated Mode! are discussed and the paper concludes with the promise that the mode! holds for sociology and the social sciences ifït is adopted.